Tourism Impacts of a Portuguese World Heritage Historic Center: Residents’ Perspectives - Vareiro, Laurentina (2016)
The World Heritage List (WHL) is widely considered a powerful tool for national tourism campaigns. Sites inscribed on the WHL by the United Nations Educational, Scientific, and Cultural Organization (UNESCO) are commonly treated as catholicons in promoting the tourism industry, which in turn helps to promote economic growth and development. This study analyzes local community perceptions of the importance of the World Heritage Site (WHS) classification of the historic center of the Portuguese city of E ́vora. The research also includes an analysis of the local residents’ perceived tourism impacts on the municipality of E ́ vora. The methodology consists of quan- titative research based on a self-administered survey applied to convenience sam- ples of local residents of the municipality of E ́ vora in the beginning of 2014. The local residents’ perceptions of the level of importance of the WHS classification to the municipality and its impact in the increase of tourists is analyzed. Positive and negative tourism impacts are then ranked and a principal components factor analysis is employed separately to the two groups of impacts in order to identify underlying dimensions associated with residents’ perceptions on tourism develop- ment. Based on the results of the factor analysis, independent sample t-tests are used to investigate differences regarding positive and negative tourism impacts between residents that live near and far from the historic center, and between residents who work/have worked in the tourism sector and residents that work/ have worked in other sectors.